2019
DOI: 10.1097/tp.0000000000002527
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free MicroRNA miR-505-3p in Graft Preservation Fluid Is an Independent Predictor of Delayed Graft Function After Kidney Transplantation

Abstract: Background Delayed graft function (DGF), a common complication after transplantation of deceased donor kidneys, affects both short- and long-term outcomes. Currently available biomarkers during graft preservation lack sensitivity in predicting risk for DGF. The aim of this study is to identify cell-free micro ribonucleic acid (miRNA) biomarkers in graft preservation fluid predictive of DGF after kidney transplantation. Methods Vascular bed preservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Importantly, we believe the major reason for the little impact of hemolysis on specific targets in our study is the distinct microRNA isolation procedure: we have performed a magnetic bead capture of microRNAs, which are isolated and purified from the serum contents, eliminating the potentially harmful effects of molecules such as hemoglobin or heparin, which are known to inhibit the PCR reaction [60][61][62][63]. Indeed, we have witnessed this effect in RNA isolated from kidney preservation fluids (described in [54]) containing heparin contamination, a commonly used anticoagulant. Our new results again demonstrate that in the bead-based capture no inhibitory effect of heparin was observed and heparinase 1 digestion did not reduce the Ct values of both endogenous and spiked-in microRNAs (Supplementary Figure S12).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, we believe the major reason for the little impact of hemolysis on specific targets in our study is the distinct microRNA isolation procedure: we have performed a magnetic bead capture of microRNAs, which are isolated and purified from the serum contents, eliminating the potentially harmful effects of molecules such as hemoglobin or heparin, which are known to inhibit the PCR reaction [60][61][62][63]. Indeed, we have witnessed this effect in RNA isolated from kidney preservation fluids (described in [54]) containing heparin contamination, a commonly used anticoagulant. Our new results again demonstrate that in the bead-based capture no inhibitory effect of heparin was observed and heparinase 1 digestion did not reduce the Ct values of both endogenous and spiked-in microRNAs (Supplementary Figure S12).…”
Section: Discussionmentioning
confidence: 93%
“…For exploring the impact of heparin contamination in microRNA quantification, a subset of graft preservation fluids (n = 8) from patients undergoing kidney transplantation (described by us in [54]) that were shown to be contaminated with heparin (n = 4) was selected, and subsequently quantified after microRNA isolation using miRNEAsy spin columns or after bead capture followed by pre-amplification. Ct values were determined and compared with or without heparinase 1 treatment.…”
Section: Hemolysis Analyses and Heparin Contaminationmentioning
confidence: 99%
“…They can be isolated, quantified and profiled by multiple platforms which can also characterize their target genes [ 32 ]. They have been studied in graft preservation fluid and proposed as viability biomarkers (miR-486-5p, miR-144-3p, miR-142-5p, and miR-144-5p) [ 12 ]; however, only miR-505-3p has been demonstrated to be an independent predictor of DGF in DCD grafts with high accuracy (AUC = 0.83) and was confirmed in a validation cohort [ 13 ].…”
Section: Iri and Dgfmentioning
confidence: 99%
“…Interestingly, cell-free miRNAs in graft preservation fluid are predictive of DGF post-transplantation. Roest HP et al identified an association between high levels of miR-505-3p in the preservation fluid of kidney grafts donated after circulatory death and an increased risk of DGF after transplantation [43]. Another prospective cohort study that analyzed graft dysfunction in transplant recipients of expanded criteria donor organs confirmed the significance of a subset of four miRNAs (miR-486-5p, miR-144-3p, miR-142-5p, and miR-144-5p) previously identified in DGF development [44].…”
Section: Post-transplant Akimentioning
confidence: 99%